Professional education, research and learning in the territory: notes on the experience of occupational therapists training - Roseli Esquerdo Lopes; Ana Paula Serrata Malfitano; Carla Regina Silva; Patrícia Leme de Oliveira Borba; Michelle Selma Hahn (O Mundo da Saúde)
We approach here occupational therapy experiences as strategies to understand social reality, to offer academic training and to develop research and reflections to promote care technologies in the social field, with a focus on strengthening social support networks of population groups in situation of social vulnerability and/or disaffiliation. That is harmonized with the proposal of training standards of World Federation of Occupational Therapists, mainly regarding the necessary engagement with the entire society, making visible the possibilities of contribution from the area to the social welfare of people in their communities. The goal is to discuss the training of undergraduate and graduate students as well as interventions that emphasize the technical-ethical-political role of professionals before contemporary social problems. For doing this, one works mainly from programs for helping Brazilian children and youngsters, in their interfaces with social questions. We observed that occupational therapy has effective contributions as a nucleus of professional specificity for intervention in the territorial dimension, for the development of conviviality, overcoming an approach centered in the clinical/individual dimension, respecting subjects’ singularity, from the principles concerning the search of the radical exercise of democracy and rights coming from citizenship.